SOME ASPECTS OF THE REGULATION OF ARTIFICIAL INTELLIGENCE - LÃ¡szlÃ³ Kerekes (Faculty of Law, Universitas Lampung, 2023)
Today, artificial intelligence is playing an increasingly important role. Isaac Asimov laid down the robotic laws of his literary universe in the science fiction classic I, Robot. In my study, I will examine how these 'laws' are reflected in the legislation of various nations-international organisations, and the justification for their regulation in legal literature-dogmatics In my study, I will present some issues related to the regulation of artificial intelligence. I will also discuss the demarcation of robotic-robotic, some concepts and some governmental regulations. In all this, I will mainly use the descriptive and comparative method. The first chapter of my thesis deals with the ontological characteristics of artificial intelligence. In the second chapter, I present the regulation of some states in the field of artificial intelligence. The third chapter examines the possible perpetrator. It is not possible to stop the development of technology for an extended period. Newer technologies contribute to a more efficient organisation of production and distribution, provide a basis for innovation in business and the amenity/recreational aspect is not negligible. It is precisely for these reasons that I see the need for legal regulation of the newer pervasive technologies. It can be seen, therefore, that the international legal system needs to be ready for the challenges of the 21st century. The research found that current EU legislation aims to guide future legislation and has incorporated a very significant part of Asimov's principles into its regulatory scope.